2015
DOI: 10.1016/j.nbd.2015.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress and lipid peroxidation are upstream of amyloid pathology

Abstract: Oxidative stress is a common feature of the aging process and of many neurodegenerative disorders, including Alzheimer’s disease. Understanding the direct causative relationship between oxidative stress and amyloid pathology, and determining the underlying molecular mechanisms is crucial for the development of more effective therapeutics for the disease. By employing microdialysis technique, we report local increase in the amyloid-β42 levels and elevated amyloid-β42/40 ratio in the interstitial fluid within 6h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
97
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(102 citation statements)
references
References 60 publications
3
97
0
2
Order By: Relevance
“…Thus, amylin dyshomeostasis induces systemic peroxidative injury independent of hyperglycemia. The link of amylin dyshomeostasis with increased lipid peroxidation may be of further relevance via its role in enzyme activities, cell signaling and gene expression [31]. …”
Section: Discussionmentioning
confidence: 99%
“…Thus, amylin dyshomeostasis induces systemic peroxidative injury independent of hyperglycemia. The link of amylin dyshomeostasis with increased lipid peroxidation may be of further relevance via its role in enzyme activities, cell signaling and gene expression [31]. …”
Section: Discussionmentioning
confidence: 99%
“…Previous studies demonstrated that toxicity of Aβ 25–35 in models of neurodegenerative diseases in vitro and in vivo was associated with the enhancement of ROS and NO liberation and oxidative damage [37,38,39,40,41], which up-regulated redox-sensitive transcription factors such as NF-κB, an important factor responsible for oxidative and inflammatory reactions in AD [42]. In agreement with these studies, Aβ 25–35 increased the ROS and NO production from SH-SY5Y cells in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…An essential brain region involved in encoding spatial memories is the CA1 subfield of the mid-and posterior hippocampus (human) or dorsal CA1 (CA1d) in rodents (3,4). A leading hypothesis in the field based on ex vivo measurements is that hippocampus oxidative stress plays a pathogenic role in spatial disorientation (2,(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16). This hypothesis has developed on the basis of studies in postmortem tissue of oxidative damage biomarkers, such as buildup of the polyunsaturated fatty acid oxidation product 4-hydroxynonenal (HNE) (17,18).…”
mentioning
confidence: 99%